Drinking settings, drinking patterns, and alcohol related harm, Perth, 1990: File pub - Lang, Ernie (ADA Dataverse, 2018)
This survey focused on people's patterns and places of drinking, and their knowledge and attitudes towards strategies aimed at minimising harm within the licensed drinking environment. The study had four main aims: first, to examine how types of drinking setting are related to different patterns of alcohol use and alcohol related problems; second, to discover the level of knowledge of laws relating to the sale and consumption of alcohol; third, to determine people's attitudes to the concept of server responsibility and server liability; and, fourth, to establish the level of community support for prevention initiatives targetted toward licensed drinking settings. The survey consisted of four parts. The first part was administered by an interviewer and asked for details of recent drinking sessions, including the venue for each session, type of alcohol consumed, quantity of alcohol, length of session, reason for drinking, satisfaction with session, mode of transport,other people present, availability of other activities and entertainment, who paid for the drinks, and usage of drugs during the session. The second part of the survey was a self-completion questionnaire assessing knowledge of alcohol-related harm and drinking offences, and views about responsibility for drinking and ways of reducing alcohol-related harm. The third part of the survey was a questionnaire completed only by respondents who drink alcohol. This questionnaire covered personal experiences of negative effects of drinking. Those who reported some negative effects were administered the fourth part of the survey, which asked for details of the relevant drinking sessions. Background variables covered by the survey were age, sex, marital status, level of education, employment status, occupation, income, and birthplace.